Food Safety During and After the Era of COVID-19 Pandemic - Olaimat, Amin N.; Shahbaz, Hafiz M.; Fatima, Nayab; Munir, Sadia; Holley, Richard A. (Frontiers in Microbiology, 2020)
The coronavirus disease 2019 (COVID-19) is a clinical syndrome caused by severe acute respiratory syndrome corona virus-2 (SARS-CoV-2). COVID-19 was declared a pandemic by the World Health Organization (WHO) on March 11, 2020 due to its rapid and extensive spread among many countries through its very contagious nature and its high mortality among the elderly and infirm. Recently, data on the survival of SARS-CoV-2 on contact surfaces has been reported, but there is none on the survival of COVID-19 on food surfaces and packages. The potential survival and transmission of SARS-CoV-2 on/via food and packages are discussed based on data available for other respiratory viruses such as SARS-CoV and MERS-CoV. However, studies are needed to explore its transmission via food and survival on food packaging materials. The implementation of food safety management systems such as Hazard Analysis and Critical Control Points (HACCP), and Good Manufacturing Practices (GMP) are important to reduce the risk of COVID-19 infection. Cleaning, sanitation, good hygienic practices, and active packaging are also needed from farm to fork.